2016
DOI: 10.1007/s11356-016-7201-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of alternating current on the adsorption of indigo carmine

Abstract: The main purpose of this work is to study the effect of a new process of accelerating which consist to couple the electrochemical process with the adsorption to remove an anionic dye, the indigo carmine. That is why, we investigated the effects of the new process of accelerating the adsorption process by using alternating current (AC) on the retention of an anionic dye, the indigo carmine. The adsorption capacity of dye (mg/g) was raised with the raise of current voltage in solution, temperature, and initial i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 63 publications
1
16
0
Order By: Relevance
“…was also confirmed by the values of the "fractional times" α, which were always lower than 1, in agreement with previous results (Kesraoui et al, 2017;Selmi et al, 2018c). When the concentration increased from 10 to 100 mg/L, the fractality increased as well, as suggested by the decrease of the values of α from 0.614 to 0.49, again in agreement with former studies (Selmi et al, 2018b).…”
Section: Kinetic Studiessupporting
confidence: 92%
“…was also confirmed by the values of the "fractional times" α, which were always lower than 1, in agreement with previous results (Kesraoui et al, 2017;Selmi et al, 2018c). When the concentration increased from 10 to 100 mg/L, the fractality increased as well, as suggested by the decrease of the values of α from 0.614 to 0.49, again in agreement with former studies (Selmi et al, 2018b).…”
Section: Kinetic Studiessupporting
confidence: 92%
“…Using the parameters of the Broeurs-Sotolongo model (γ, n and τ), the half sorption time (τ 50% ) can be determined according to the following equation [48,49]:τ50%=sans-serifτ(2(normaln1)(normaln1)(normaln1))1/sans-serifγ…”
Section: Resultsmentioning
confidence: 99%
“…32,35,65 The parameter a describes the fractal properties of a non-uniform system and its adsorption mechanisms. 35,65,66 While the parameter c is related to the agglomeration on the adsorbent surface, it gives an idea of the degree of heterogeneity of the adsorbent surface. Furthermore, it has been shown that an increase in the c value indicates a decrease in surface heterogeneity or the opposite.…”
Section: Bpa Adsorption Isothermsmentioning
confidence: 99%